(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the concepts of polysemy, synonymy, and homonymy in the Uzbek language and discusses the principles of their integration into an electronic thesaurus. It explores the organization of lexical-semantic relations using the WordNet model and evaluates their significance in natural language processing (NLP). The paper also analyzes the contextual use of polysemous words, the classification of synonym groups, and the incorporation of homonymous units into digital systems. The findings contribute both theoretically and practically to the creation of an Uzbek language electronic thesaurus.